2004
DOI: 10.1016/j.jacc.2003.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diabetes and diabetes-gender interaction on the risk of death in patients hospitalized with congestive heart failure

Abstract: Diabetes is a potent, independent risk factor for mortality in patients hospitalized with HF. The excess risk in diabetic patients appears to be particularly prominent in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
120
7
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(157 citation statements)
references
References 35 publications
20
120
7
8
Order By: Relevance
“…we did not adjust for the number of tests performed), we found a sex difference in the prognostic importance of high HbA 1c levels on the risk of all-cause mortality; it was greater in women than in men, in agreement with the findings from a Framingham sub-study, and previous large cohort studies of heart failure patients and myocardial infarction patients, where diabetes was found to carry a worse prognosis in women than in men [29][30][31]. What may underlie these findings is not clear, but they may relate to a higher prevalence of high HbA 1c values as was found in women from the SCOUT trial.…”
Section: Discussionsupporting
confidence: 89%
“…we did not adjust for the number of tests performed), we found a sex difference in the prognostic importance of high HbA 1c levels on the risk of all-cause mortality; it was greater in women than in men, in agreement with the findings from a Framingham sub-study, and previous large cohort studies of heart failure patients and myocardial infarction patients, where diabetes was found to carry a worse prognosis in women than in men [29][30][31]. What may underlie these findings is not clear, but they may relate to a higher prevalence of high HbA 1c values as was found in women from the SCOUT trial.…”
Section: Discussionsupporting
confidence: 89%
“…Diagnosis of diabetes was based on a self-report by the patient or by documentation in the patient's medical records 22 . Possible explanations of higher prevalence of diabetes in North American subjects are differences in the etiology of HF in those populations.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of DM in patients with HF has been associated with an increased risk of poor outcomes 11,22,[31][32][33][34] . An analysis from the Studies of Left Ventricular Dysfunction trials and registry program demonstrated that the presence of DM in patients with HF resulted in an increased risk for mortality 31 .…”
Section: Discussionmentioning
confidence: 99%
“…W badaniach BEST i Studies Of Left Ventricular Dysfunction (SOLVD) opisywano cukrzycę jako niezależny czynnik prognostyczny zgonu (u większości pacjentów występowała HF o podłożu niedokrwiennym) [390,392]. Również w badaniach Danish Investigations and Arrhythmia ON Dofetilide (DIAMOND) i Candesartan in Heart Failure Assessment of Reduction in Mortality and Morbidity (CHARM) wykazano, że cukrzyca jest niezależnym czynnikiem predykcyjnym zgonu, niezależnie od przyczyny [393,394].…”
Section: Cukrzyca I Niewydolność Sercaunclassified